Molybdenum sputtering target, method for producing same, and method for producing sputtering film using molybdenum sputtering target
By adopting plastic processing and heat treatment processes in the manufacturing process of molybdenum sputtering targets, the problem that high-density and low-oxygen content of molybdenum sputtering targets in the prior art is difficult to achieve fine grains, and the target materials with high-density, low-oxygen content and fine grains are realized, reducing the particle generation during film formation.
Patent Information
- Application Number
- CN202380062625.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-02
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-11
AI Technical Summary
While the existing molybdenum sputtering targets are high in density and low in oxygen, it is difficult to achieve fine grain size, resulting in a large amount of particles generated during film formation.
In the manufacturing process of the molybdenum sputtering target, plastic processing and heat treatment are adopted, and the finening process includes plastic processing and heat treatment, to reduce the grain size and control the oxygen content to below 100 mass ppm.
The molybdenum sputtering target has fine grains while having high density and low oxygen content, which significantly reduces the particle generation during film formation.
Smart Images

Figure CN119816619A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a molybdenum sputtering target, a method for producing the same, and a method for producing a sputtering film using the molybdenum sputtering target. Background Art
[0002] Sputtering targets (hereinafter also referred to as "targets") containing metals such as molybdenum are used for forming light-shielding films for photolithography masks, etc. With the development of photolithography technology, the required properties of targets have also become higher. Currently, targets that can further reduce the generation of impurity particles such as metal oxides (so-called particles) during the formation of sputtered films are required. To reduce the amount of particles generated, studies have been conducted so far on high density, low oxidation, and miniaturization of the crystal grain size of the target.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-154814
[0006] Patent Document 2: International Publication No. 2012 / 043227
[0007] Patent Document 3: Japanese Patent Application Publication No. 2000-045066 Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] Recently, in order to further reduce particles, a molybdenum sputtering target having high density and low oxygen content and fine crystal grains is required. However, it is difficult to reduce the crystal grain size in a target having high density and low oxygen content.
[0010] Generally, in the sintering of molybdenum powder with high density or low oxygen content, the grains grow and the grain diameter tends to become larger. In detail, if hot isostatic pressing (hereinafter also referred to as "HIP") sintering of molybdenum is performed under high temperature and high pressure conditions so that the obtained target is high density, the grains will grow significantly. In addition, in the sintering of molybdenum with low oxygen content, there are few impurities that hinder grain growth, so the grains will grow significantly in the same way. In this way, high density and miniaturization of grain size, and low oxygen quantification and miniaturization of grain size are in a relationship of one increasing while the other decreasing.
[0011] For example, in Patent Document 1, Comparative Examples 1 and 2 and Comparative Examples 7 and 8 report targets having fine grain sizes of 2 μm and 8 μm on average, but the density is not sufficiently increased and arc discharge is likely to occur.
[0012] In Patent Document 2, as Example No. 27, a target with an oxygen content of 85 ppm is reported, but Figure 5The average particle size measured by the SEM image of MgCl2O3 was about 15 μm.
[0013] Patent Document 3 reports that the density of the molybdenum sintered body immediately after HIP sintering is 100% and the average grain size is 11 μm. As described above, in the sintered body immediately after sintering, the high density and the fine grain size are in a trade-off relationship, and it is difficult to further reduce the grain size by HIP sintering alone.
[0014] In any of the documents, there is no report on a molybdenum sputtering target having high density, low oxygen content and fine crystal grains.
[0015] The object of the present invention is to provide at least one of a molybdenum sputtering target, a method for manufacturing the same, and a method for manufacturing a sputtering film using the same, wherein the molybdenum sputtering target has high density and low oxygen content, has fine grains, and reduces the generation of particles during film formation.
[0016] Technical solutions for solving technical problems
[0017] That is, the present invention is as described in the claims; furthermore, the gist of the present disclosure is as follows.
[0018] (1) A molybdenum sputtering target comprising molybdenum, including crystal grains having an average crystal grain size of less than 10 μm, a relative density of 99.6% or more, and an oxygen content of 100 mass ppm or less.
[0019] (2) The molybdenum sputtering target according to (1), wherein the purity is 99.9% or more.
[0020] (3) The molybdenum sputtering target according to (1) or (2), wherein a maximum deviation of an average grain size of the crystal grains in a depth direction is 3 μm or less.
[0021] (4) The molybdenum sputtering target according to (3), wherein the maximum deviation is less than 1 μm.
[0022] (5) The molybdenum sputtering target according to (4), wherein the maximum deviation is 0.2 μm or less.
[0023] (6) The molybdenum sputtering target according to any one of (1) to (5), wherein the average crystal grain size is 5 μm or less.
[0024] (7) The molybdenum sputtering target according to any one of (1) to (6), wherein the average KAM value is 0.5° or less.
[0025] (8) The molybdenum sputtering target according to any one of (1) to (7), wherein the area of the sputtering surface is 200 cm 2 above.
[0026] (9) A method for producing a sputtered film, comprising: producing a sputtered film by sputtering using the molybdenum sputtering target described in any one of (1) to (8).
[0027] (10) A method for manufacturing a molybdenum sputtering target, which is a method for manufacturing the molybdenum sputtering target described in any one of (1) to (8), comprising a miniaturization process for miniaturizing grains in a molybdenum ingot, wherein the miniaturization process comprises: a plastic processing process, wherein the molybdenum ingot is subjected to plastic processing to obtain a plastic processed body; and a heat treatment process, wherein the plastic processed body is subjected to heat treatment.
[0028] Effects of the Invention
[0029] According to the present invention, at least one of a molybdenum sputtering target, a method for manufacturing the same, and a method for manufacturing a sputtered film using the molybdenum sputtering target is provided, wherein the molybdenum sputtering target has fine grains while being high in density and low in oxygen content and reduces the generation of particles during film formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic plan view of a target for explaining the observation area A.
[0031] Figure 2 1 is a schematic cross-sectional view of a target for explaining the sampling portion B.
[0032] Figure 3 This is a cross-sectional view showing a substrate with a sputtered film produced by one embodiment of the method for producing a sputtered film of the present invention.
[0033] Figure 4 This is a diagram showing a SEM observation image of a sampling portion B in the cross section of the target of Example 1.
[0034] Figure 5 This is a diagram showing a SEM observation image of a sample portion B in the cross section of Comparative Example 1. DETAILED DESCRIPTION
[0035] Although one embodiment of the present invention is shown and described in detail, the present invention is not limited to the following embodiment.
[0036] In addition, various compositions and parameters disclosed in the present specification can be set as any combination, and the upper limits and lower limits of the values disclosed in the present specification can be set as any combination.
[0037] <Molybdenum sputtering target>
[0038] The target of the present embodiment is a molybdenum sputtering target containing molybdenum. The target of the present embodiment is more preferably a metal sputtering target composed of molybdenum.
[0039] The oxygen content of the target of the present embodiment is less than 100 mass ppm, more preferably less than 30 mass ppm, further preferably less than 20 mass ppm, further preferably less than 10 mass ppm, and particularly preferably less than 7 mass ppm. By making the oxygen content of the target within the above range, it is possible to reduce the mixing of oxygen in the film during film formation and suppress the generation of particles caused by the mixing of oxygen. Furthermore, the target of the present embodiment can obtain a sputtered film with higher crystallinity. The oxygen content can be 0 mass ppm or more, greater than 0 mass ppm, 0.1 mass ppm or more, 0.5 mass ppm or more, or 1 mass ppm or more. The oxygen content is preferably 0 mass ppm or more and 100 mass ppm or less, more preferably greater than 0 mass ppm and less than 30 mass ppm, and further preferably 0.1 mass ppm or more and 20 mass ppm or less.
[0040] The oxygen content of the target can be measured by an oxygen and nitrogen analyzer (device name: ON736, manufactured by LECO).
[0041] The target of the present embodiment contains crystal grains, and the average grain size (average grain size) of the crystal grains is less than 10 μm, more preferably less than 8 μm, more preferably less than 5 μm, more preferably less than 4 μm, and particularly preferably less than 2 μm. The average grain size is greater than 0 μm, preferably greater than 0.1 μm or greater than 1 μm. The average grain size is preferably greater than 0 μm and less than 8 μm, more preferably greater than 0.1 μm and less than 5 μm, and more preferably greater than 1 μm and less than 4 μm.
[0042] By setting the average crystal grain size to a range of less than 10 μm, the generation of particles during film formation can be reduced, and abnormal discharge can be suppressed, and the detachment of reattached sputtered particles can be suppressed.
[0043] The average grain size can be determined by scanning electron microscopy-electron backscatter diffraction (hereinafter also referred to as "SEM-EBSD"), observing the target structure under the following measurement conditions and using the program, and using the analysis program (such as Aztec Crystal) to analyze all the observed grains. Specifically, the rotation angle between adjacent measurement points based on EBSD, that is, the orientation difference (°) between the measurement points is measured in the SEM image, and the loop line with a continuous and uninterrupted pixel boundary with a rotation angle greater than 10° is regarded as a grain boundary, and the area within the loop line is regarded as one grain. The diameter of a circle with an area equivalent to the area of the region constituting the grain is taken as the grain size of the grain, and the arithmetic mean of all the measured grains is calculated as the average grain size.
[0044] (Measurement conditions)
[0045] Beam conditions: acceleration voltage 20 kV, irradiation current 100 μA
[0046] Working distance: 10mm
[0047] (Use the program)
[0048] Assay procedure: AZtec
[0049] Analytical Procedure: AZtec Crystal
[0050] Figure 1 and Figure 2 A schematic diagram of the target is shown in FIG. Figure 1 2 is a schematic top view of a target for explaining an observation area A. Figure 2 Schematic diagram of the cross section of the target for explaining the sampling portion B. The shape of the target is not particularly limited. Figure 1 and Figure 2 In the description, the target is a disk. Figure 2 In the embodiment, the sputtering surface 11 is the surface facing the substrate or other film-forming object during film formation and is the surface in contact with the plasma-generated atmosphere gas. In contrast, the bonding surface 12 is the surface that is bonded to the backing plate. Figure 2 As shown, the sputtering surface 11 and the bonding surface 12 both correspond to the plane of the disk (hereinafter, for convenience, the sputtering surface is also referred to as the "front surface" and the bonding surface is also referred to as the "back surface").
[0051] like Figure 1 As shown, the annular area in the circular sputtering surface 11 of the target 1 is taken as the observation area A. The observation area A is the area sandwiched between a circle with O as the center and a radius of 0.5R and a circle with O as the center and a radius of 0.75R, when the distance from the center O to the periphery (the radius of the circular sputtering surface 11) is denoted as R. In the case where the sputtering surface of the target is rectangular, it is the area sandwiched between a rectangle with P as the intersection of the diagonals and a distance to the periphery of 0.5PQ and a rectangle with P as the intersection of the diagonals and a distance to the periphery of 0.75PQ, when the distance from the intersection P of the diagonals to a point Q on the periphery of the rectangle is denoted as PQ. The area of width 5 mm × total thickness t (mm) in the cross section 13 of the observation area A is taken as the sampling portion B (refer to Figure 2 ), for the sampling portion B, the average grain size can be obtained by SEM-EBSD. The sampling portion B can be arbitrarily selected as long as it is within the observation area A. It should be noted that in this specification, the case of cutting the target parallel to the sputtering surface and dividing it is described later, and for this divided body, similar to the sampling portion B, the area with a width of 5mm×the total thickness t'(mm) of the divided body is called "sampling portion B'". The measurement conditions and usage procedures of SEM-EBSD are as follows.
[0052] (Measurement conditions)
[0053] Beam conditions: acceleration voltage 20 kV, irradiation current 100 μA
[0054] Working distance: 10mm
[0055] (Use the program)
[0056] Assay procedure: AZtec
[0057] Analytical Procedure: AZtec Crystal
[0058] When measuring the average grain size, the target is cut using a conventional cutting method (for example, a cutting method using at least one of a fine cutter and a water jet) to expose the cross section to prepare the sample. Before the measurement, the sample is mirror-polished with SiC grinding paper and buffing (Japanese: buffing), and then pre-treated by electrolytic etching with a 5 volume % sulfuric acid aqueous solution.
[0059] The average KAM value of the target of the present embodiment is preferably less than 1 °, more preferably less than 0.5 ° or less than 0.4 °. Thus, the strain inside the target is reduced, the cracking and warping during mechanical processing are suppressed, and during film formation, the cracking and particle generation of the sputtering surface of the target are easily suppressed, and the etching rate is stabilized. The average KAM value is calculated by the arithmetic mean of the KAM values of all measurement points. The average KAM value can be cited as more than 0 ° or more than 0.1 °. The average KAM value is preferably more than 0 ° and less than 1 °, more preferably more than 0 ° and less than 0.5 °, and more preferably more than 0.1 ° and less than 0.4 °.
[0060] The maximum deviation of the average grain size in the depth direction of the target of this embodiment (hereinafter, also referred to as "maximum deviation") is preferably 3 μm or less, and more preferably 1 μm or less. By making the maximum deviation 3 μm or less, the film forming rate of the sputtered film is easy to become uniform. The maximum deviation can be less than 1 μm, 0.8 μm or less, 0.6 μm or less, 0.4 μm or less, 0.2 μm or less, or 0.1 μm or less.
[0061] The maximum deviation may be 0 μm or more, 0.01 μm or more, 0.03 μm or more, or 0.05 μm or more. The maximum deviation is preferably 0 μm or more and 3 μm or less, more preferably 0.01 μm or more and less than 1 μm, and further preferably 0.03 μm or more and 0.2 μm or less.
[0062] Here, the depth direction refers to the thickness direction of the target. The maximum deviation of the average grain size in the depth direction refers to the maximum deviation between the average grain sizes on the surface of the sputtering surface side of the sampling portion B' of each segment when the target is divided into three parts in parallel with the sputtering surface in the depth direction. Regarding the maximum deviation, for example, after cutting the target, the surface of each segment is ground, and the average grain size is calculated in each segment, and the difference between the maximum value and the minimum value is taken as the maximum deviation.
[0063] The relative density of the target of this embodiment is 99.6% or more, preferably 99.7% or more, 99.8% or more, 99.9% or more, 99.95% or more, or 99.99% or more. If the relative density is less than 99.6%, particles are likely to be generated. By making the relative density higher than 99.6%, the strength of the target is improved, and it is easy to apply a high discharge power to the target. Thus, by increasing the film formation rate when the sputtered film is formed by sputtering the target, the productivity of the sputtered film is easily increased. The relative density is 100% or less. The relative density is preferably 99.6% or more and 100% or less, more preferably 99.9% or more and 100% or less, and further preferably 99.99% or more and 100% or less.
[0064] The relative density of the target can be calculated by the following method. That is, the measured density of the target is measured according to JIS R 1634, and the measured density is divided by the true density to calculate the relative density. In this embodiment, the true density of molybdenum is 10.22 g / cm 3 That's it.
[0065] The area of the sputtering surface of the target in this embodiment is not particularly limited, but is preferably 200 cm 2 More than 350cm 2 More preferably, 800 cm 2 By making the area of the sputtering surface 200cm 2 As a result, the film-forming area of the sputtered film can be increased. As a result, a large-area film that usually requires the use of multiple targets for film formation can also be formed by a single target. Furthermore, the mixing of impurities from the boundary between targets can be suppressed. The upper limit of the area of the sputtering surface is not particularly limited, for example, 3000 cm 2 , 2000cm 2 or 1500cm 2 The area of the sputtering surface can be calculated using the diameter of the sputtering surface as the area of a circle. The diameter of the sputtering surface can be measured using a vernier caliper or a coordinate measuring machine. The area of the sputtering surface is preferably 200 cm 2 Above and 3000cm 2 Below, more preferably 350cm 2 Above and 3000cm 2Below, more preferably 800cm 2 Above and 2000cm 2 the following.
[0066] The purity of the target of the present embodiment is not particularly limited, and is preferably 99.9% or more, more preferably 99.99% or more, and further preferably 99.995% or more. "The purity of the target is 99.9% or more" means that the content of molybdenum metal contained in the target of the present embodiment is 99.9% or more by mass, that is, the content of metal elements (impurity metal elements) other than molybdenum metal contained in the target of the present embodiment is 0.1% or less by mass. By making the purity 99.9% or more, it is easier to suppress the generation of particles starting from impurities. It should be noted that, regarding the expression of purity, "4N" means a purity of 99.99% or more, "5N" means a purity of 99.999% or more, and "4N8" means a purity of 99.998% or more. In addition, in this specification, the purity of the target is calculated only based on the metal element in both the powder and the sintered body, and the oxygen content is not included.
[0067] The purity of the target of the present embodiment can be measured by glow discharge mass spectrometry (GDMS). For example, a test piece of 10 to 25 mm × 10 to 25 mm × 0.5 to 15 mm is cut out from the target as a measurement sample. The measurement sample is ground with SiC grinding paper (#800), ultrasonically cleaned in pure water for 10 minutes, dehydrated with alcohol and dried with hot air, and then vacuum packaged to perform pretreatment. For the measurement sample after pretreatment, the content of impurities (impurity metal elements) is measured using the method according to ASTM F 1593, and the purity is calculated based on the content of the impurities and the following formula.
[0068] Purity (%) = 100 - impurity content
[0069] <Method for producing sputtering target>
[0070] Next, a method for producing a target according to the present embodiment will be described.
[0071] The target of the present embodiment can be manufactured by a method having a miniaturization process, wherein the miniaturization process includes: a plastic working process, wherein a molybdenum ingot is subjected to plastic working to obtain a plastic worked body; and a heat treatment process, wherein the plastic worked body is subjected to heat treatment. That is, the method for manufacturing the target of the present embodiment includes a miniaturization process for miniaturizing the crystal grains in the molybdenum ingot, wherein the miniaturization process includes: a plastic working process, wherein the molybdenum ingot is subjected to plastic working to obtain a plastic worked body; and a heat treatment process, wherein the plastic worked body is subjected to heat treatment.
[0072] Furthermore, the target manufacturing method of the present embodiment may include an ingot manufacturing step of obtaining an ingot by sintering or melting molybdenum metal (hereinafter also referred to as “raw material” or “raw material metal”) and then cooling it before the above-mentioned miniaturization step.
[0073] (Ingot production process)
[0074] In the ingot manufacturing process, an ingot is manufactured from a raw material by a sintering method or a melting method.
[0075] The raw material may be in any form as long as it can be sintered or melted and then cooled to obtain an ingot, and such a form may be, for example, a powdery form, a granular form, or a flake form.
[0076] The purity of the raw metal is preferably 99.99% or more. In addition, the oxygen content of the raw material is 100 mass ppm or less, preferably 30 mass ppm or less, more preferably 20 mass ppm or less, further preferably 10 mass ppm or less, and particularly preferably 7 mass ppm or less. By reducing the oxygen content of the raw material, the oxygen content of the target can be reduced. The oxygen content is preferably small, but can be greater than 0 mass ppm, and further greater than 1 mass ppm. The oxygen content of the raw material is preferably greater than 0 mass ppm and less than 100 mass ppm, more preferably greater than 0 mass ppm and less than 30 mass ppm, and further preferably greater than 1 mass ppm and less than 20 mass ppm.
[0077] In the sintering method, an ingot is obtained by sintering the raw material. As the type of sintering method, for example, at least any one of a molding sintering method and a pressure sintering method can be cited. Any sintering method can be used, but in order to increase the density, a pressure sintering method is preferably used. As a pressure sintering method, a hot pressing method, a hot isostatic pressing (Hot Isostatic Press) method (hereinafter also referred to as a "HIP method"), etc. can be cited, and it is preferred to use a HIP method with a higher pressurizing capacity. The sintering temperature is not particularly limited, and is preferably above 1000°C and below 1500°C, and more preferably above 1200°C and below 1450°C. By making the sintering temperature within the above-mentioned temperature range, the density of the sintered body before the rolling process and the average grain size can be within a specific range. The obtained sintered body can be used as an ingot.
[0078] In the smelting method, the raw material is heated to a temperature above the melting point to melt it, and then cooled to obtain an ingot. The melting method is not particularly limited as long as it is a method that makes the oxygen content of the target 100 mass ppm or less, and for example, one or more selected from the group consisting of condensed shell melting, arc melting and electron beam melting can be cited. In order to reduce the oxygen content and impurities of the target, electron beam melting is preferred.
[0079] The relative density of the ingot to be subjected to the plastic working step is preferably 90% or more, more preferably 95% or more. By making the relative density of the ingot 90% or more, the strength of the target obtained from the ingot is improved. The relative density of the ingot can be exemplified as 100% or less. The relative density of the ingot is preferably 90% or more and 100% or less, more preferably 95% or more and 100% or less.
[0080] The average grain size of the ingot is preferably 10 μm or more and 400 μm or less. By making the average grain size 10 μm or more, the density of the target obtained is improved. If the average grain size of the ingot is 400 μm or less, the average grain size of the target obtained is easy to become smaller, and the number of plastic working treatments described later is reduced, and the productivity of the target is improved.
[0081] (Micro-refining process)
[0082] The miniaturization step is a step of miniaturizing the crystal grains in the molybdenum ingot. The miniaturization step includes: a plastic working step, in which the molybdenum ingot is plastically worked to obtain a plastic worked body; and a heat treatment step, in which the plastic worked body is heat treated. By subjecting the ingot to the miniaturization step, the crystal grains in the ingot are miniaturized, and the target of the present embodiment having an average crystal grain size of less than 10 μm is obtained.
[0083] In the plastic working step, the ingot is plastically worked to produce a plastic worked body. By further subjecting the obtained plastic worked body to a heat treatment step, the crystal grains of the ingot are refined to obtain the target of the present embodiment. In addition, the ingot may be ground into a shape and size suitable for plastic working before the plastic working treatment. As a processing method, grinding using a surface grinder may be cited, for example.
[0084] The means of plastic working is not particularly limited as long as it is a method that can destroy the crystal structure of the ingot, for example, rolling rollers can be used. In rolling using rolling rollers, the manufactured ingot is compressed by passing through the gap between a pair of rolling rollers whose width is smaller than the thickness of the ingot. Thus, a rolled body is obtained. The obtained rolled body can also be repeatedly passed through the gap between a pair of rolling rollers. Hereinafter, the process of passing the ingot or the rolled body through the gap between a pair of rolling rollers is also referred to as a "rolling pass".
[0085] The rolling process is preferably carried out at a temperature of the ingot to be rolled (hereinafter also referred to as "rolling temperature") of 200°C or more and 1500°C or less, more preferably 500°C or more and 1200°C or less, and further preferably 700°C or more and 1000°C or less. By setting the rolling temperature within the above range, strain can be left in the entire rolled plate (rolled body), so that the grains are easily refined in the subsequent heat treatment. By setting the rolling temperature to 500°C or more, the occurrence of cracks can be suppressed; by setting the rolling temperature to 1200°C or less, the coarsening of grains due to dynamic recrystallization can be suppressed.
[0086] In addition, the reduction rate of the ingot for each rolling pass is preferably set to be 6% or more and 20% or less relative to the thickness before the rolling pass, and more preferably 8% or more and 10% or less. If the reduction rate is 6% or more, the difference between the deformation amount of the surface and the inside of the ingot during rolling is small, and the orientation deviation in the depth direction after recrystallization can be suppressed. If the reduction rate is 20% or less, the cracking of the material can be suppressed. By setting the reduction rate to 6% or more and 20% or less, the rolled body will not crack, strain can be uniformly introduced into the whole, and rolling with controlled orientation deviation can be performed.
[0087] The temperature difference between the rolling rolls and the ingot is preferably 500° C. or less, more preferably 300° C. or less. If the temperature difference between the rolls and the ingot is 500° C. or less, the occurrence of cracks due to thermal stress caused by the temperature gradient inside the ingot can be suppressed.
[0088] By further subjecting the plastically worked body obtained by plastic working to a heat treatment step, a heat-treated body with refined crystal grains can be obtained.
[0089] The heat treatment in the heat treatment step is performed at a temperature higher than the plastic working temperature in the previous plastic working step. By performing the heat treatment at a temperature higher than the plastic working temperature, the strain introduced during the plastic working can be released and the metal structure of the molybdenum can be recrystallized.
[0090] The heat treatment temperature is preferably above 500°C and below 1300°C, preferably above 700°C and below 1100°C. This promotes the recrystallization of the metal structure and refines the target grains. If the plastically processed body is heated below 1300°C in a vacuum or inert gas atmosphere furnace, there is a tendency that surface oxidation can be suppressed and the average grain size is not easy to increase, and the target of this embodiment is easy to obtain. By setting the heat treatment temperature to above 500°C, the deformation texture after plastic processing can be recrystallized, and a uniform recrystallized structure can be obtained. Through the above-mentioned heat treatment process, a heat-treated body can be obtained.
[0091] It should be noted that the miniaturization process can also be repeated. That is, the heat-treated body obtained by subjecting the plastic processed body to the heat treatment process after the above-mentioned plastic processing process can be again supplied to the plastic processing process and the heat treatment process. In the case of repeated miniaturization processes, it is preferred that the plastic processing temperature in the second and subsequent miniaturization processes is lower than the plastic processing temperature of the ingot or plastic processed body in the previous miniaturization process. Specifically, the plastic processing temperature is preferably above 300°C and less than 800°C. By performing plastic processing at a temperature lower than that of the previous miniaturization process, it is possible to further add strain while appropriately maintaining the strain accumulated in the ingot or plastic processed body in the previous miniaturization process, so that strain can be uniformly applied to the interior of the material, and the grains can be miniaturized to reduce the grain size of the grains.
[0092] Sometimes, oxides are generated on the surface of the heat-treated body after the miniaturization process, and the surface roughness of the heat-treated body is large. Therefore, it is preferred that the heat-treated body is subjected to surface grinding. The processing method is not particularly limited, and grinding using a surface grinder can be cited. In order to remove the oxide scale on the surface of the heat-treated body, it is preferred that the cutting depth from the surface of the heat-treated body is more than 0.5 mm. In the case of repeating the miniaturization process, at least the heat-treated body after the last heat treatment process is subjected to surface grinding.
[0093] Through these treatments, the target of this embodiment can be obtained.
[0094] The target thus obtained can be used by bonding to a backing plate. Examples of the bonding method include diffusion bonding, solder bonding, and friction stir bonding, but the bonding method is not particularly limited.
[0095] <Sputtering film manufacturing method>
[0096] Next, a method for producing a sputtered film according to the present embodiment will be described.
[0097] The method for manufacturing a sputtered film of the present embodiment includes a step of manufacturing a sputtered film by sputtering using the target of the present embodiment. Figure 3 As shown, the substrate with a sputtered film 100 includes a substrate 10 and a sputtered film 20 formed on the substrate 10. By performing sputtering using the target of the present embodiment, generation of particles is suppressed during film formation, and a sputtered film having high film thickness uniformity can be provided.
[0098] The substrate 10 is not particularly limited, and examples thereof include a glass substrate and a quartz substrate.
[0099] The temperature of the substrate 10 (film formation temperature) is not particularly limited, and may be, for example, room temperature (25° C.).
[0100] The process gas during film formation is not particularly limited as long as it is a gas type that generates sputtering by discharge, and may be argon, for example.
[0101] The gas partial pressure during film formation is not particularly limited, and may be, for example, 0.2 Pa or more and 2 Pa or less.
[0102] The discharge output during film formation is not particularly limited, and can be, for example, 2.5 W / cm 2 Above and 50W / cm 2 the following.
[0103] The film formation time is not particularly limited, and may be, for example, 10 sec to 100 sec.
[0104] The sputtering can be performed using a conventional sputtering device. The conditions for the sputtering are not particularly limited, and the sputtering can be performed, for example, under the following conditions.
[0105] Ultimate vacuum degree: 1×10 -4 Pa
[0106] Process gas: Ar
[0107] Gas partial pressure: 0.5Pa
[0108] Film forming temperature: room temperature
[0109] Substrate: Glass substrate
[0110] Discharge output: 10W / cm 2
[0111] Film forming time: 60 sec
[0112] Example
[0113] The present disclosure will be described in more detail below with reference to examples and comparative examples, but the present disclosure is not limited to the following examples.
[0114] (Example 1)
[0115] 210 kg of molybdenum powder (purity 5N (ie, purity 99.999% or more), oxygen content 15 mass ppm) was sealed in a 350 mm×350 mm×350 mm soft iron pot and subjected to HIP treatment under the following conditions.
[0116] HIP treatment atmosphere: Argon atmosphere
[0117] HIP treatment temperature: 1250℃
[0118] HIP processing pressure: 150MPa
[0119] HIP treatment time: 5 hours
[0120] The obtained HIP-treated body was taken out from the pot, and the shape was adjusted by grinding and cutting to obtain a disk-shaped ingot with a diameter of 180 mm and a thickness of 50 mm.
[0121] After the obtained ingot is heated to 800°C, the heated ingot is plastically worked in such a manner that the compression rate in the thickness direction does not exceed 10 mm / second. In addition, during the processing, when the material temperature drops below 500°C, the ingot is reheated for 10 minutes in a furnace at 800°C, and the plastic working is repeatedly performed until the size becomes 330 mm in diameter × 15 mm in thickness (that is, until the total reduction rate reaches 70%), thereby obtaining a plastic worked body.
[0122] The obtained plastically processed body (processed ingot) was heat treated in a hydrogen atmosphere at a heat treatment temperature of 900°C for 3 hours (180 minutes) to obtain a circular plate-shaped molybdenum material with a diameter of 330 mm and a thickness of 15 mm (hereinafter also referred to as a "target"), which was used as the target of this example.
[0123] (Example 2)
[0124] 210 kg of molybdenum powder (purity 5N, oxygen content 15 mass ppm) was sealed in a 350 mm×350 mm×350 mm soft iron pot and subjected to HIP treatment under the following conditions.
[0125] HIP treatment atmosphere: Argon atmosphere
[0126] HIP treatment temperature: 1250℃
[0127] HIP processing pressure: 150MPa
[0128] HIP treatment time: 5 hours
[0129] The obtained HIP-treated body was taken out from the pot, and the shape was adjusted by grinding and cutting to obtain a disk-shaped ingot with a diameter of 180 mm and a thickness of 50 mm.
[0130] After the obtained ingot is heated to 1200°C, the heated ingot is plastically worked in a manner that the compression speed (pressing speed) in the plate thickness direction does not exceed 10 mm / second (i.e., the maximum pressing speed is 10 mm / second). In addition, during the processing, when the material temperature drops below 900°C, the ingot is reheated for 10 minutes in a furnace at 1200°C, and the plastic working is repeatedly performed until the size becomes 330 mm in diameter × 15 mm in thickness (i.e., until the total reduction rate reaches 70%), thereby obtaining a plastic worked body.
[0131] The obtained plastically worked body (worked ingot) was heat treated in a hydrogen atmosphere at a heat treatment temperature of 1100° C. for 3 hours (180 minutes) to obtain a disk-shaped target of 330 mm in diameter×15 mm in thickness, which was used as the target of this example.
[0132] (Comparative Example 1)
[0133] 210 kg of molybdenum powder (purity 4N8, oxygen content 10 mass ppm) was sealed in a 350 mm×350 mm×350 mm soft iron pot and subjected to HIP treatment under the following conditions.
[0134] HIP treatment atmosphere: Argon atmosphere
[0135] HIP treatment temperature: 1250℃
[0136] HIP processing pressure: 150MPa
[0137] HIP treatment time: 5 hours
[0138] The obtained HIP-treated body was taken out from the pot, and the shape was adjusted by grinding and cutting to obtain a disk-shaped ingot with a diameter of 180 mm and a thickness of 50 mm.
[0139] After the obtained ingot is heated to 1350°C, the heated ingot is plastically worked in such a manner that the compression rate in the thickness direction does not exceed 25 mm / second. In addition, during the processing, when the material temperature drops below 1100°C, the ingot is reheated for 10 minutes in a furnace at 1350°C, and the plastic working is repeatedly performed until the size becomes 330 mm in diameter × 15 mm in thickness (that is, until the total reduction rate reaches 70%), thereby obtaining a plastic worked body.
[0140] The obtained plastically worked body (worked ingot) was heat treated in a hydrogen atmosphere at a heat treatment temperature of 1400° C. for 1 hour (60 minutes) to obtain a disk-shaped target of 330 mm in diameter×15 mm in thickness, which was used as the target of this example.
[0141] (Comparative Example 2)
[0142] 210 kg of molybdenum powder (purity 4N8, oxygen content 10 mass ppm) was sealed in a 350 mm×350 mm×350 mm soft iron pot and subjected to HIP treatment under the following conditions.
[0143] HIP treatment atmosphere: Argon atmosphere
[0144] HIP treatment temperature: 1250℃
[0145] HIP processing pressure: 150MPa
[0146] HIP treatment time: 5 hours
[0147] The obtained HIP-treated body was taken out from the pot, and the shape was adjusted by grinding and cutting to obtain a disk-shaped ingot with a diameter of 180 mm and a thickness of 50 mm.
[0148] After the obtained ingot is heated to 1350°C, the heated ingot is plastically worked in such a manner that the compression rate in the thickness direction does not exceed 25 mm / second. In addition, during the processing, when the material temperature drops below 1100°C, the ingot is reheated for 10 minutes in a furnace at 1350°C, and the plastic working is repeatedly performed until the size becomes 330 mm in diameter × 15 mm in thickness (that is, until the total reduction rate reaches 70%), thereby obtaining a plastic worked body.
[0149] The obtained plastically worked body (worked ingot) was heat treated in a hydrogen atmosphere at a heat treatment temperature of 1500° C. for 1 hour (60 minutes) to obtain a disk-shaped target of 330 mm in diameter×15 mm in thickness, which was used as the target of this example.
[0150] <Evaluation of Target>
[0151] (Scanning Electron Microscopy-Electron Backscatter Diffraction)
[0152] In scanning electron microscopy-electron backscatter diffraction (SEM-EBSD), relative to the radius R of the circular sputtering surface of the disk-shaped target, a portion (sampling portion) of a width of 5 mm radially inward from a position 0.7R away from the center of the circle × the total target thickness t (mm) is observed. The measurement pretreatment, measurement conditions and usage procedures of SEM-EBSD are as follows. In addition, Figure 4 and Figure 5 SEM observation images of the sampling portion B in the cross section of the targets of Example 1 and Comparative Example 1 are shown.
[0153] ·Assay pretreatment
[0154] After mirror polishing with SiC polishing paper and buffing, pretreatment was performed by electrolytic etching with a 5 vol % sulfuric acid aqueous solution.
[0155] ·Assay conditions and usage procedures
[0156] (Measurement conditions)
[0157] The measurement conditions and procedures of SEM-EBSD are shown below.
[0158] Device name: JSM-IT800 (manufactured by JEOL Ltd.)
[0159] Beam conditions: acceleration voltage 20 kV, irradiation current 100 μA
[0160] Working distance: 10mm
[0161] Step size: 20nm (Example 1), 200nm (Example 2), 6μm (Comparative Example 1),
[0162] 12μm (Comparative Example 2)
[0163] (Use the program)
[0164] Assay procedure: AZtec
[0165] Analytical Procedure: AZtec Crystal
[0166] (purity)
[0167] The purity of the target is determined by glow discharge mass spectrometry (GDMS). Specifically, a test piece of 10 mm × 10 mm × 5 mm is cut out from the target as a test sample. After the test sample is ground with SiC grinding paper (#800), it is ultrasonically cleaned in pure water for 10 minutes, dehydrated with alcohol and dried with hot air, and then vacuum packaged, thereby pre-treated. For the pre-treated test sample, the content (mass %) of impurities (impurity metal elements) is determined by the method according to ASTM F 1593. Then, the purity is calculated based on the following formula. The results are shown in Table 2.
[0168] Purity (%) = 100 - impurity content
[0169] (oxygen content)
[0170] The oxygen content of the target was measured by an oxygen and nitrogen analyzer (device name: ON736, manufactured by LECO). At this time, a 4 mm×4 mm×5 mm prism-shaped sample cut out from the target by cutting was used as the measurement object. The results are shown in Table 2.
[0171] (Average grain size)
[0172] The average grain size was determined using SEM-EBSD (SEM: manufactured by JEOL Ltd., EBSD: manufactured by Oxford Instruments). The target structure was observed using the following measurement conditions and procedures, and all observed grains were analyzed using the analysis program (Aztec Crystal). Specifically, the rotation angle between adjacent measurement points based on EBSD, that is, the orientation difference (°) between the measurement points, was measured in the SEM image, and the loop line with a continuous and uninterrupted pixel boundary with a rotation angle greater than 10° was regarded as a grain boundary, and the area within the loop line was regarded as one grain. The diameter of a circle with an area equivalent to the area of the region constituting the grain is taken as the grain size of the grain, and the arithmetic mean of all the measured grains is calculated as the average grain size. The results are shown in Table 2.
[0173] (Measurement conditions)
[0174] Beam conditions: acceleration voltage 20 kV, irradiation current 100 μA
[0175] Working distance: 10mm
[0176] (Use the program)
[0177] Assay procedure: AZtec
[0178] Analytical Procedure: AZtec Crystal
[0179] (Maximum deviation of average grain size)
[0180] The target was divided into three equal parts in the depth direction by a precision cutter parallel to the sputtering surface to obtain three divided bodies. For the obtained three divided bodies, the surface was polished, and the average grain size in the surface on the sputtering surface side of the sampling part B' was calculated, and the difference between the maximum and minimum values was calculated as the maximum deviation (μm). The results are shown in Table 2.
[0181] (Determination of relative density)
[0182] The density of the target was measured according to JIS R 1634 (Determination of density and open porosity of sintered bodies of fine ceramics). The true density of molybdenum was 10.22 g / cm 3 The relative density (%) was calculated based on the results shown in Table 2.
[0183] (Average KAM value)
[0184] The KAM (Kernel Average Misorientation) values were measured at all the measurement points in the sampling portion B, and the arithmetic mean of the KAM values obtained at all the measurement points was calculated, and the arithmetic mean was used as the average KAM value of the target of each embodiment or each comparative example. The results are shown in Table 2.
[0185] [Table 1]
[0186]
[0187] [Table 2]
[0188]
[0189] In Table 1, in the targets of each embodiment in which the ingot miniaturization process was performed under the manufacturing conditions shown in Table 1, it was confirmed that the relative density was 99.6% or more, the average grain size was less than 10 μm, and the oxygen content was 100 mass ppm or less, as shown in Table 2. On the other hand, in the targets of the comparative examples, as shown in Table 2, although the relative density was high, the average grain size was greater than 100 μm. Therefore, it is considered that the targets of each embodiment have high density and low oxygen content, and have finer grains than the targets of each comparative example, so it is easier to reduce the generation of particles during film formation.
[0190] Description of Reference Numerals
[0191] 1…Sputtering target
[0192] 10…Substrate
[0193] 11…Sputtering surface
[0194] 12…Joint surface
[0195] 13… Section
[0196] 20…Sputtered film
[0197] 100…Substrate with sputtered film
[0198] A…Observation Area
[0199] B…Sampling part
[0200] It should be noted that this application is based on Japanese Patent Application (Japanese Patent Application No. 2022-140343) filed on September 2, 2022, the entirety of which is incorporated herein by reference. In addition, all references cited herein are incorporated as a whole.
Claims
1. A molybdenum sputtering target, characterized in that: The steel sheet contains molybdenum and has crystal grains with an average crystal grain size of less than 10 μm, a relative density of 99.6% or more, and an oxygen content of 100 mass ppm or less.
2. The molybdenum sputtering target according to claim 1, wherein The purity of the molybdenum sputtering target is above 99.9%.
3. The molybdenum sputtering target according to claim 1 or 2, wherein: The molybdenum sputtering target has a maximum deviation of an average grain size of the crystal grains in a depth direction of 3 μm or less.
4. The molybdenum sputtering target according to claim 3, wherein The maximum deviation is less than 1 μm.
5. The molybdenum sputtering target according to claim 4, wherein The maximum deviation is less than 0.2 μm.
6. The molybdenum sputtering target according to any one of claims 1 to 5, wherein The average grain size is 5 μm or less.
7. The molybdenum sputtering target according to any one of claims 1 to 6, wherein The average KAM value of the molybdenum sputtering target is less than 0.5°.
8. The molybdenum sputtering target according to any one of claims 1 to 7, wherein The sputtering surface area of the molybdenum sputtering target is 200 cm 2 above.
9. A method for manufacturing a sputtered film, characterized in that: A sputtered film is produced by sputtering using the molybdenum sputtering target according to any one of claims 1 to 8.
10. The method for producing a molybdenum sputtering target according to any one of claims 1 to 8, characterized in that: This includes a process for refining the crystal grains in the molybdenum ingot. The miniaturization process includes: A plastic working step, wherein the molybdenum ingot is plastically worked to obtain a plastic worked body; and The heat treatment step includes heating the plastically processed body.
Citation Information
Patent Citations
Mo-based target material and its production
JP2000045066A
Sputtering target, manufacturing method therefor, and thin film produced with the use of the method
JP2005154814A
Microwave irradiation device
JP2022140343A
Method for producing molybdenum target
WO2012043227A1